Progress of global ARAIM availability of BDS-2/BDS-3 with TGD and ISB. Issue 4 (15th August 2022) - Ma, Xiaping; He, Xiaoxing; Yu, Kegen; Montillet, Jean-Philippe; Lu, Tieding; Yan, Li; Zhao, Lidu
Abstract: Advanced RAIM (ARAIM) is an extension of Receiver Autonomous Integrity Monitoring (RAIM) by enhancing the vertical navigation capabilities, so it can be applied to higher-level precision applications. But when the observation data of the second-generation BDS (BDS-2) and the third-generation BDS (BDS-3) are combined to evaluate the ARAIM availability, the evaluation be affected by the Timing Group Delay (TGD) of different satellite signals and the Inter-system Bias (ISB) between BDS-2 and BDS-3, which is ignored by the existing literature. Therefore, in this article, we deduced the mathematical model of ARAIM and the calculation formula of Vertical Protection Level (VPL) by considering the combined influence of TGD and ISB. We used the BDS observation data and ephemeris files of 374 International GNSS Service (IGS) stations around world on July 29, 2021 to calculate the VPL of these stations and evaluate the global ARAIM availability. The results show that the number of visible BDS satellites is 8.033 and the Geometric Dilution of Precision (GDOP) is 1.721, which can meet the basic needs of global ARAIM calculations. Furthermore, when considering the combined influence of TGD and ISB, the evaluation of ARAIM availability by Multiple Hypothesis Solution Separation (MHSS) is significantly better than that without considering the combined TGD and ISB influence or their individual influence. The average VPL values at these IGS stations in four cases are 124.925 m, 13.882 m, 32.610 m and 9.962 m, and the corresponding ARAIM availability percentages are 90.839%, 95.241%, 96.751% and 99.660%, respectively. Finally, the minimum coverage of ARAIM availability based on BDS can reach 90.839%, which can meet the aviation demand for ARAIM availability in most regions and times.